2010
DOI: 10.1182/blood-2010-03-272393
|View full text |Cite
|
Sign up to set email alerts
|

Tipifarnib sensitizes cells to proteasome inhibition by blocking degradation of bortezomib-induced aggresomes

Abstract: In this report, we investigated the mechanism responsible for synergistic induction of myeloma cell apoptosis induced by the combination of tipifarnib and bortezomib. Immunofluorescence studies revealed that bortezomib alone resulted in an accumulation of puncta of ubiquitinated proteins that was further enhanced by the addition of tipifarnib. These data suggest inhibition of the degradation of bortezomib-induced aggresomes; and consistent with this possibility, we also observed an increase in p62SQSTM1 in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Mechanistic studies showed that the anti-MM activity of this combination is due to caspase activation and Mcl-1 downregulation, which result in apoptotic cell death, distinct from the autophagic cell death previously observed with single-agent FK866 treatment. 7,8,45 The lack of autophagy triggered by combined therapy suggests that lower doses of drugs used here are unable to activate or sustain autophagy but can activate apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies showed that the anti-MM activity of this combination is due to caspase activation and Mcl-1 downregulation, which result in apoptotic cell death, distinct from the autophagic cell death previously observed with single-agent FK866 treatment. 7,8,45 The lack of autophagy triggered by combined therapy suggests that lower doses of drugs used here are unable to activate or sustain autophagy but can activate apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The peritoneal macrophages were primed and stimulated as described in MATERIALS AND METHODS. GM-130, calnexin, α-tubulin, early endosome antigen 1 (EEA1), vimentin, and γ-tubulin were used as markers of Golgi apparatus, endoplasmic reticulum, microtubule, endosome, phagosome, and centromere, respectively (Webb et al, 2001;Latz et al, 2004;Eng et al, 2007;David et al, 2010;Wolff et al, 2011;Yuan et al, 2012). Lysotracker was applied for lysosome detection.…”
Section: Asc Pyroptosome Did Not Co-localize With Other Detected Orgamentioning
confidence: 99%
“…In addition to the NFkB pathway, previous studies have indicated that bortezomib also induces autophagy (43)(44)(45). Therefore, we analyzed whether MAP17 could also alter this process.…”
Section: Levels Of the Map17 Oncogene Determine The Sensitivity To Bomentioning
confidence: 99%